Leadership in Action : Issues and Observations - For Women Leaders in Korea, Gains but Miles to Go - Kim, YangHee (Center for Creative Leadership, 2005)
Although women in Korea constitute 40.7 percent of the total labor force, they fill only 7 percent of managerial and executive posts.